2017
DOI: 10.1111/rge.12132
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemistry of Granitoids in Sibolga and its Surrounding Areas, North Sumatra, Indonesia

Abstract: Petrochemical studies were conducted on granitoids in Sibolga and surrounding areas in North Sumatra, Indonesia. The granitoids presented the characteristics of A‐ and I‐type ilmenite series. The syenogranites from Sarudik, the syenogranite, quartz syenite, and quartz alkali feldspar syenite from Sibuluhan Sihaporas, and the monzogranites from Sibolga Julu are A‐type granitoids that have high SiO2, CaO, Al2O3, Na2O + K2O, and Rb content, a high FeO/MgO ratio, and low Ba, Sr, and Zr content. The alkali feldspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…The occurrence of the Sarudik A2‐type granites, together with the graben‐horst structural style, implies a magmatic event triggered by post‐collisional extension during the late Triassic, which may explain the existence of closely coeval granitoids in Sijunjung (206 ±3 Ma, biotite K‐Ar) (Silitonga & Kastowo, 1975), Sulit Air (203 ±6 Ma, biotite K‐Ar) (McCourt & Cobbing, 1993), Sungei Isahan (197 ±2 Ma, muscovite K‐Ar) (Schwartz, 1987) and Sibolga (206–219 Ma, hornblende and biotite K‐Ar) (Aspden et al, 1982; Fontaine & Gafoer, 1989). The deduction also shows the flaw in the model proposed by Setiawan et al (2017), who suggested that the A‐type granitoids in Sibolga were formed in continental rift setting during the Triassic.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The occurrence of the Sarudik A2‐type granites, together with the graben‐horst structural style, implies a magmatic event triggered by post‐collisional extension during the late Triassic, which may explain the existence of closely coeval granitoids in Sijunjung (206 ±3 Ma, biotite K‐Ar) (Silitonga & Kastowo, 1975), Sulit Air (203 ±6 Ma, biotite K‐Ar) (McCourt & Cobbing, 1993), Sungei Isahan (197 ±2 Ma, muscovite K‐Ar) (Schwartz, 1987) and Sibolga (206–219 Ma, hornblende and biotite K‐Ar) (Aspden et al, 1982; Fontaine & Gafoer, 1989). The deduction also shows the flaw in the model proposed by Setiawan et al (2017), who suggested that the A‐type granitoids in Sibolga were formed in continental rift setting during the Triassic.…”
Section: Discussionmentioning
confidence: 62%
“…3 As suggested by Barber et al (2005) Cobbing, 1993), Sungei Isahan (197 ±2 Ma, muscovite K-Ar) (Schwartz, 1987) and Sibolga (206-219 Ma, hornblende and biotite K-Ar) (Aspden et al, 1982;Fontaine & Gafoer, 1989). The deduction also shows the flaw in the model proposed by Setiawan et al (2017), who suggested that the A-type granitoids in Sibolga were formed in continental rift setting during the Triassic.…”
Section: Tectonic Implicationsmentioning
confidence: 69%
See 1 more Smart Citation
“…Three Tethyan oceans were involved in the development of the Southeast Asia terranes, namely, the Devonian-Triassic Palaeo-Tethys, the Early Permian-Late Cretaceous Meso-Tethys, and the Late Triassic-Late Cretaceous Ceno-Tethys (Jiang et al, 2017;Hutchinson, 2014;Metcalfe, 2013). The subduction of the Indian Plate beneath Asia was considered to have initiated in the Eocene (Ali and Aitchison, 2005;Irzon et al, 2018;Setiawan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Mesozoic intrusions in Sumatra are I-type, subduction-associated, and situated in the Barisan Mountains (Barber, 2000;McCourt et al, 1996;Zhang et al, 2018). However, several studies notified the presence of anorogenic A-type intrusions, namely Sibolga Granite (Setiawan et al, 2017;Zhang et al, 2020) and Sijunjung Granite (Irzon et al, 2018) in the central Sumatra region. Therefore, more complete petrography and geochemistry data on these plutons are required to explain the tectonic history of Sumatra.…”
Section: Introductionmentioning
confidence: 99%